Sudden and persistent disphonia in the framework of COVID-19: the case report of a nurse (2020)
In December 2019, clusters of atypical pneumonia with unknown etiology emerged in the city of Wuhan in China. In early January 2020, the Center for Disease Control in China announced that it was identified a new coronavirus, first tentatively named 2019-nCoV and officially named SARSCoV-2 by the International Committee on Taxonomy of Viruses. On 11 February 2020 the WHO identified the disease caused by SARS-CoV-2 as COVID-19 (COronaVIrus Disease-19 based on the year of appearance). Although only a few months have passed since the beginning of this pandemic, numerous studies, case reports, reviews by leading international scientific and medical journals have been published. However, given the unpredictability of virus behaviour and the still limited knowledge about it, many aspects of the infection are still little known. A recent epidemiological study has shown the presence of dysphonia in some patients with COVID-19, with a minority reporting aphonia during the clinical course of the disease. This case study draws attention on a 50-year-old female nurse presented with a history of fatigue for small efforts and persistent dysphonia at the Occupational Health Department of a major University Hospital in central Italy. The patient had a history of COVID-19 infection, which lasted about two months with pulmonary and extrapulmonary symptoms. After two RT-PCR negativities for SARS-CoV-2, dysphonia and fatigue due to minor efforts persisted. The patient, following the persistence of the symptomatology, carried out numerous specialist examinations, which showed no organic alterations. Based on her clinical and instrumental history, we hypothesized a psychogenetic dysphonia related to COVID-19. This case report highlights the importance of personalized medicine with long-term follow-up and good psychological support in patients who tested positive for COVID-19 and in particular in the categories at greatest risk of both contagion and adverse physical and mental outcomes like health care workers.